Estimation of Minimum Viable Population of Long-tailed Macaques (Macaca fascicularis Raffles 1821) in Support of Wildlife Management in Ir. H. Djuanda Grand Forest Park - Hatta Vrazila; Elham Sumarga; Hikmat Ramdan (School of Life Sciences and Technology, Institut Teknologi Bandung, 2022)
Most long-tailed macaques (LTMs) in Southeast Asia are commensal animals, which means they can coexist and benefit from humans. This interaction potentially triggers disturbance and disease transmission caused by LTMs, for instance, in Ir. Djuanda Grand Forest Park (GFP). A previous study indicates an overpopulation of LTMs in this area. The need for population control of this macaque requires appropriate ecological considerations, including determining the minimum viable population (MVP). This study aims to estimate the MVP of LTMs in Ir. Djuanda GFP area is the key input for its population control scheme. The MVP is determined based on population growth simulation using the Lefkovitch matrix. In combination with the estimate of population growth, the MVP was used to formulate the population control scheme of LTMs, by considering the current wildlife management regulations and the perception of Ir. Djuanda GFP area manager obtained through interviews. This study found six groups of LTMs in Ir. Djuanda GFP with a total population of 229 individuals, a sex ratio of 1:1.05, an age class ratio of infants, juveniles, sub-adults, and adults of 16.6%:25.7%:32,3%:25.3%, and a population growth rate of 19.7%/year. The estimate of MVP of this primate is 230 individuals, with an average group size of 38 individuals and an age class ratio of infants, juveniles, sub-adults, and adults 30%:9.1%:27.4%:23.5%. Based on wildlife management regulations and area manager perceptions, population control schemes can be implemented for relocation and captive purposes. The population control scheme consists of an age-class control scheme and a group control scheme. The age-class control scheme controls the population by 334 individuals, while the colony control scheme controls 406 individuals.